Identification of electrical breakdown faults in shunt capacitor bank elements using instantaneous negative sequence current - Wenhai Zhang; Yuzhe Li; Wen Xiao; Shu Zhang; Xianyong Xiao (International Journal of Electrical Power & Energy Systems)
Electrical breakdown faults (EBFs) in shunt capacitor banks (SCB) elements always occur near the transient overvoltage peak induced by the energization of SCBs. Accurate and timely detection of EBFs is vital to effectively monitor the condition of SCBs. Due to the subtle changes in capacitance, the steady and transient characteristics of voltage and current caused by EBFs are weak compared to the transients caused by capacitor switching. The accurate identification of EBFs is extremely challenging. However, sudden changes in imbalance caused by EBFs can lead to abrupt changes in the negative sequence current. This study uses the transient mutation characteristics of the instantaneous negative sequence current (INSC) triggered by EBFs to effectively identify such faults. Specifically, this study analyzes the transient current changes in the fault phase caused by the EBF and calculates the INSC based on an improved instantaneous symmetrical component method. A mutation-detecting algorithm with three continuous samples is then used to detect changes in the INSC. Extensive simulation results using PSCAD/EMTDC validate the accuracy and reliability of the proposed method under various operational conditions, providing an effective and practical means for EBF identification to realize SCB condition monitoring and enhancing the overall reliability of power systems.